2019
DOI: 10.1007/s12035-019-01767-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Carbon Nanomaterials with Metals for Bio-sensing Applications

Abstract: Age structure in most developed countries is changing fast as the average lifespan is increasing significantly, calling for solutions to provide improved treatments for age-related neurological diseases and disorders. In order to address these problems, a reliable way of recording information about neurotransmitters from in vitro and in vivo applications is needed to better understand neurological diseases and disorders as well as currently used treatments. Likewise, recent developments in medicine, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…We have previously shown that the metal catalysts in carbon nanomaterials have an essential role in the sensitivity and selectivity towards a different biomolecules, which cannot be achieved only with pure carbon. [15,16] Furthermore, we have extensively studied the suitability of pristine iron containing single-walled carbon nanotubes (SWCNTs) for the detection of various analgesics. [7][8][9] Despite these studies, at this stage, there are no clear indications regarding the required amount of iron that enhances electrocatalysis towards opioids, and whether the electrocatalytic properties of Fe-SWCNTs be improved with simple oxidative pretreatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the metal catalysts in carbon nanomaterials have an essential role in the sensitivity and selectivity towards a different biomolecules, which cannot be achieved only with pure carbon. [15,16] Furthermore, we have extensively studied the suitability of pristine iron containing single-walled carbon nanotubes (SWCNTs) for the detection of various analgesics. [7][8][9] Despite these studies, at this stage, there are no clear indications regarding the required amount of iron that enhances electrocatalysis towards opioids, and whether the electrocatalytic properties of Fe-SWCNTs be improved with simple oxidative pretreatment.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that metals can catalyze various electrochemical reactions. We have previously shown that the metal catalysts in carbon nanomaterials have an essential role in the sensitivity and selectivity towards a different biomolecules, which cannot be achieved only with pure carbon . Furthermore, we have extensively studied the suitability of pristine iron containing single‐walled carbon nanotubes (SWCNTs) for the detection of various analgesics .…”
Section: Introductionmentioning
confidence: 99%
“…They are also very promising for tissue engineering [ 54 ], especially for bone [ 55 ], and for conductive cells, such as the cardiac [ 56 , 57 ] and nerve tissues [ 58 , 59 ]. Their potential uses in clinical applications [ 60 ] and sensing [ 61 ] have been recently reviewed. Therefore, this article will focus solely on the very latest developments regarding innovative biomedical uses of carbon nanomaterials in the form of smart hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they have attracted great interest for their innovative potential in areas of unmet clinical need [ 74 , 76 ], such as oncology [ 77 ], infections [ 78 ], and tissue engineering [ 79 ], especially for conductive nerve [ 80 , 81 ] and cardiac [ 82 , 83 ] tissues, but also bone [ 84 ]. Their potential applications in sensing [ 85 ] and, generally, in clinical applications [ 86 ] are also widely studied.…”
Section: Introductionmentioning
confidence: 99%